The Mediation Role of Islamic Social Reporting in the Effect of Good Corporate Governance on Financial Sustainability: The Case of the Indonesia Islamic Bank - Akbar, Taufik; Taqi, Muhammad; Machfudzhoh, Asih (Universitas Mercu Buana, 2022)
Sustainable finance aims to increase the resilience and competitiveness of Financial Services Institutions to grow and develop sustainably. The development of the Islamic banking business in Indonesia in terms of income earned is still categorized as relatively small compared to conventional banking. Therefore, Islamic banking must improve the performance of its company to grow and develop so that it can compete with conventional banking. This study aims to examine the effect of Good Corporate Governance (GCG) on the Financial Sustainability Ratio (FSR), as well as examine the role of Islamic Social Reporting (ISR) at Indonesia Islamic Bank in influencing the relationship between Good Corporate Governance (GCG) and Financial Sustainability Ratio (FSR). The research method used is a quantitative approach with an analytical method using the Structural Equation Model Partial Least Square (SEM PLS). The subjects in this study were Indonesian Islamic Commercial Banks registered with the Financial Services Authority (OJK) in 2013 - 2019. The direct test results showed that GCG disclosure had a negative and insignificant effect on FSR, then GCG disclosure had a negative and insignificant impact on ISR. ISR disclosure has a positive and significant effect on FSR. The indirect test results show that ISR cannot mediate the relationship between GCG and FSR